Pengembangan Media Pembelajaran Artsteps Berbantuan Lagu Pada Materi Siklus Hidup Hewan - Sari, Vinny Juwika; Sutikno, Putri Yanuarita (Jurnal Penelitian Pendidikan IPA, 2024)
The inequality of student learning outcomes in the science and science content on animal life cycles and the learning media used by teachers in schools is still not optimal. Thus, interactive media is needed so that learning can run optimally, namely Artsteps using songs. This research aims to develop, and test the feasibility and the effectiveness of Artsteps learning media using songs in improving learning outcomes on animal life cycle for class IV. This type of research is Research and Development (R&D) which uses the Borg and Gall development model. The result of this research is the process of developing song-assisted Artsteps as a learning medium on animal life cycle material; the feasibility of song-assisted Artsteps which is considered very valid by experts with an average validation value of 91%; student responses to song-assisted Artsteps were very valid with a percentage of 95%; The results of the t-test show a sig (2-tailed) value of 0.000 < 0.05 and it is stated that there is a difference in the average results before treatment and in the limited test and extensive test, so it can be concluded that Artsteps using songs can improve learning outcomes on animal life cycle.